Investigating the verbal working memory network in children with Dyslexia : an effective connectivity study - Kwok, Fu Yu (2018)
Most of the existing theories of dyslexia have been based on the behavioural deficits and aberrant neural activity observed in individuals with dyslexia. However, growing evidence has pointed towards a possible deficit in the effective network connectivity, whereby a shift in directional modulatory connectivity from one region to another is documented. Thus, the present dissertation aimed to explicate the impact of dyslexia on the effective connectivity network during verbal working memory using dynamic causal modeling (DCM). Throughout the thesis, three lines of investigation were conducted. Study 1 set the stage for the dissertation by extending the verbal working memory network established by Chen and Desmond (2005a) to elucidate the effective network connectivity in typical adults during verbal working memory. The results were consistent with previous studies, demonstrating activations at both the cortical and subcortical regions. Notably, results from the Bayesian model selection analysis indicated that the data obtained from the typical adult population showed a better fit for the model where the connectivity pathway from the left inferior frontal gyrus (IFG) to the left inferior parietal lobule (IPL) was modulated in addition to the modulatory effects on both the frontal/superior cerebellar articulatory control system and the parietal/inferior cerebellar phonological storage system. Subsequently, Study 2a examined the underlying neural network during verbal working memory in typically developing children. Reduced neural activity was observed across all the regions of interest. Additionally, an analysis of hemispheric laterality showed a left-cerebro right-cerebellar lateralisation, which is similar to that documented in the adult population. Moving beyond functional activation, results revealed unique dynamics in effective connectivity, whereby data obtained from the typically developing children population displayed a better fit for the model with unilateral modulatory effect on three distinct pathways: (1) from the inferior frontal gyrus to the inferior parietal lobule, (2) the frontal/superior cerebellar articulatory pathway and (3) the parietal/inferior cerebellar phonological storage pathway. These findings were similar to that of adults. Lastly, study 2b examined how dyslexia contributes to the differences in effective connectivity pathway during verbal working memory in the pediatric population. Results indicated that, in comparison to typically developing children, children with dyslexia displayed significantly reduced activation at both the inferior and superior cerebellum. Consistent with the functional activation results, Bayesian model selection showed that the data obtained from the children with dyslexia indicated a slight better fit for the model with only modulatory effects from the left inferior frontal gyrus (IFG) to the left inferior parietal lobule (IPL). Further analysis revealed that the data obtained from the children with dyslexia showed a better fit for models without modulatory connectivity from the cortical to subcortical regions. Taken together, this dissertation shed light on the effective connectivity between one neuronal region to another within the verbal working memory network in three distinct populations. It has advanced present knowledge of the influence of cross-sectional age-related effects, and the contributions of dyslexia on the effective connectivity network during verbal working memory. More importantly, the results from the study support the case for a new hypothesis that may provide a more holistic explanation of the deficits observed in dyslexia: the cerebro-cerebellar network theory of dyslexia. In conclusion, the findings from the present dissertation serve as a springboard for future studies which aim to explore the possible differences in network connectivity pathways used by children with dyslexia using different task paradigms. More importantly, the study provided important implications that may facilitate the development of more targeted interventions for dyslexia.